2019
DOI: 10.1111/jch.13756
|View full text |Cite
|
Sign up to set email alerts
|

Effect of hypertension status on the association between sleep duration and stroke among middle‐aged and elderly population

Abstract: We aimed to examine whether hypertension status modified the association between sleep duration and stroke among middle‐aged and elderly population. This cross‐sectional study included 10 516 participants aged ≥45 years from the China Hypertension Survey study. Sleep duration and history of stroke were assessed by questionnaires. Multivariate logistic regression analyses, a generalized additive model (GAM) and smooth curve fitting (penalized spline method) and a two‐piecewise logistic regression models were pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…A comparison of short sleep (� 6h) and long sleep duration (>8 h) were compared to normal sleep duration (6-8 h). Although this normal duration differs slightly from the recommendations of the US National Sleep Foundation and American Academy of Sleep Medicine [44], the proposed 6-8 h "normal" sleep duration for this population comes from recent studies of the association between sleep duration and CVD events in Chinese population [45,46].…”
Section: Plos Onementioning
confidence: 82%
“…A comparison of short sleep (� 6h) and long sleep duration (>8 h) were compared to normal sleep duration (6-8 h). Although this normal duration differs slightly from the recommendations of the US National Sleep Foundation and American Academy of Sleep Medicine [44], the proposed 6-8 h "normal" sleep duration for this population comes from recent studies of the association between sleep duration and CVD events in Chinese population [45,46].…”
Section: Plos Onementioning
confidence: 82%
“…The outcome was stroke (ischemic or hemorrhagic), excluding strokes caused by transient ischemic attacks (TIA), craniocerebral trauma, and intracranial tumors. 20 In this study, the medical history of stroke was a self-reported stroke, which was mainly collected through a questionnaire. By asking each participant whether there was a stroke, if so, when the stroke occurred, the symptoms at that time, what kind of treatment, and whether there were relevant medical records included discharge summary and imaging data.…”
Section: Discussionmentioning
confidence: 99%
“…The outcome was stroke (ischemic or hemorrhagic), excluding strokes caused by transient ischemic attacks (TIA), craniocerebral trauma, and intracranial tumors 20 . In this study, the medical history of stroke was a self‐reported stroke, which was mainly collected through a questionnaire.…”
Section: Methodsmentioning
confidence: 99%
“…4,5 In the current issue of The Journal of Clinical Hypertension, the study by Dr Hua and colleagues aimed to examine the association between sleep duration and stroke risk in middle-aged and elderly population. 6 The cross-sectional study included 10 516 participants aged ≥45 years from the China Hypertension Survey study, a nationally representative cross-sectional survey designed to provide reliable and evidence-based data on the current status of hypertension and associated factors in Chinese adults. Longer sleep duration was associated with higher prevalence of stroke: the relationship resulted linear in non-hypertensive patients with a turning point of the smooth curve at 8 hours, whereas a threshold effect was found in hypertensive individuals.…”
mentioning
confidence: 99%
“…Longer sleep duration was associated with higher prevalence of stroke: the relationship resulted linear in non-hypertensive patients with a turning point of the smooth curve at 8 hours, whereas a threshold effect was found in hypertensive individuals. 6 Despite methodological issues inherent to the cross-sectional and self-reported nature of data, which may be subjected to recall biases and possible residual or unmeasured confounders, the study can offer intriguing insights for the understanding of behavioral contributors to stroke.…”
mentioning
confidence: 99%